Role of yoga prana vidya healing techniques in successful and speedy recovery of orthopaedic cases of bone injuries and fractures: a multiple case study - Shah, Saloni D.; M., Atheesh Kumar; Nanduri, Venkata S. (International Journal of Research in Orthopaedics, 2021)
Bones form a vital part of the skeletal system providing mechanical support, strength, structure and protection to the human body. Inability of the bone to resist any kind of stress caused accidently can result in a bone injury or a fracture. This article provides a summary of eleven cases of bone injury and fracture treated successfully by yoga prana vidya (YPV) techniques as a complementary medicine for faster recovery. The study was carried out by two healers who independently healed eleven cases of bone injury and fracture using the bone regeneration techniques of YPV. Further, the data was collected and the results were analysed. By application of YPV healing techniques complementarily, it is observed that full recovery took place within 10 days to 45 days for the 3 hospitalised cases, and within 3 to 8 days for the two patients who had bandage/dressing done at a medical facility. In case of the remaining 6 patients who sought YPV healing help in preference to seeking medical help the recovery took place within 5 to 20 days. helping the patients to lead a normal life thereafter. It is observed that YPV techniques can be used for faster recovery of patients with injured and fractured bones. This paper shows the successful results when the techniques were applied on eleven participants. It is recommended to conduct further studies on a larger scale for the healing of bone related cases such as injury and fractures.